SOCIAL ECONOMY AS THE BASIS OF INCLUSIVE DEVELOPMENT OF THE SOCIAL SPHERE - Zherеbylo, Іryna (Socio-economic relations in the digital society, 2020)
The article reveals the economic essence of the concept of «social economy». The place and role of the social economy in the development of the social sphere in European countries are substantiated. Emphasis is placed on strengthening the issue of development of social enterprises as the main subjects of the social economy at the level of the European Union and other supranational formations, international organizations and states. Characteristic features and spheres of functioning of social enterprises in European countries are determined. It is shown that the composition of social enterprises in Europe includes: enterprises for which the provision of social services and the achievement of the common good is the goal of commercial activity, often in the form of social innovation; enterprises that reinvest profits in order to achieve social goals; enterprises, the system of ownership or management of which is formed on the basis of democratic participatory principles. The list of subjects of social economy is given; identified the main areas of their operation: industry, agriculture, energy, housing, construction, digital economy, innovative development, education, health, culture, sports, social security, banking, insurance. Typification of social enterprises is substantiated. Problematic aspects in the field of state support and support of social enterprises, which negatively affect the distribution of entities and hinder their development, have been identified. The sources of financial support for the development of social enterprises in European countries are studied, among which the role of the state as the main consumer of goods and services produced by social enterprises is highlighted. The classification of sources of financing of social enterprises into public and private finances is substantiated. The directions of stimulating the development and spread of social enterprises in Ukraine and the main advantages of implementing the concept of social economy and social enterprises in ensuring socio-economic development and development of the social sphere in the country are substantiated. It is proved that for Ukraine the issue of social economy development is an effective basis for diversification and improving the quality of social services to the population.
Keywords: social economy; social enterprise; social sphere; public finances; financial support of social entrepreneurship